Peran Gereja dalam Menanggapi isu Kesehatan Mental - Naya Aurora Smith; Intan Sakti Pius X (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
Mental health is one of the most difficult problems to solve. In Indonesia, data shows that 6.1% of the Indonesian population aged 15 years and above experience mental health disorders. Many of them are isolated, judged, and socially isolated because of the bad stigma of mental health disorders, because the church has a principle to respect the dignity of human beings who are created gloriously as the image and likeness of God (Genesis 1:17). In the teachings of the church, we are called to love them "as ourselves" as in Gaudium et Spes art. 27 by taking care of their lives and the means they need to live and be treated properly. This research aims to show the role of the church for those who are suffering from mental health disorders. This research uses the literature study method by exploring journals, books, and documents both in print and electronic form as well as other data sources relevant to the research. In this case the church has a role to be present to accompany them in the form of services in Catholic church communities to continue to support those who are struggling in suffering.